Hot deformation and dynamic recrystallization behaviours of a Nb–Ti bearing HSLA steel simulated by compact strip production process - Zhixiang Fu; Gengwei Yang; Xinping Mao; Ruyang Han; Yaowen Xu; Deming Xu (Journal of Materials Research and Technology)
The hot deformation and dynamic recrystallization (DRX) behaviours of a Nb–Ti bearing HSLA steel simulated by the compact strip production (CSP) process were investigated with the deformation interval of 900–1150 °C/0.01–10 s−1. According to the peak stress, the constitutive equation was constructed, and the hot deformation activation energy (Qdef) was determined to be 447.153 kJ/mol. Based upon the analysis of the hot processing maps for various true strains, high deformation temperatures or true strain, along with low strain rates are favorable for obtaining a high power dissipation coefficient (η), which promotes the DRX and enhances the hot workability. With the deformation interval changed from 900 °C/0.01–1 s−1 and 950 °C/0.1–1 s−1 to 950 °C/0.01 s−1 and 1000–1150 °C/0.01–10 s−1, the softening mechanism transitioned from discontinuous DRX (DDRX) to continuous DRX (CDRX) + DDRX, the corresponding microstructure transitioned from necklace structure to equiaxed DRX grain. Moreover, the DRX critical strain model and grain size model were constructed based on Z parameter, which has a high degree of validity and accuracy.